PENGARUH KONSEP DIRI, EFIKASI DIRI, DAN INTERNAL LOCUS OF CONTROL TERHADAP KEMATANGAN KARIR (Studi pada Brand Partner Oriflame di Jakarta) - Azalea, Arneta; Paulina, Paulina (Ibs Press, 2024)
This study aims to test and analyze the influence of self-concept, self-efficacy, and internal locus of control on the maturity of study careers at Oriflame Brand Partners in Jakarta. This research aims to examine and analyze the influence of self-concept, self-efficacy, and internal locus of control on the career maturity of Oriflame Brand Partners. In this research, there are independent variables, namely self-concept, self-efficacy, and internal locus of control which have an influence on the dependent variable, namely career maturity. Hypothesis testing in this research uses the PLS or Partial Least Square method with SmartPLS 3.0 software. The data collection technique uses a Google Form application questionnaire to collect respondent information. The sample in this research is the Oriflame Brand Partner in Jakarta who is currently active in 2024. The results of the analysis show that self-concept has no effect on career maturity. Self-efficacy has no effect on career maturity. Internal locus of control influences career maturity.